Fluid-rock interaction in carbonatite and alkaline composite intrusions and implications for rare earth element mineralization - Ozturk, Anil (My University, 2019)
The Spitskop Igneous Complex is a carbonatite-alkaline silicate complex located 190 km northeast of Pretoria and 48 km east of Groblersdal in South Africa. It covers an area of 50 km2 and intruded into the Bushveld Complex on the Kaapvaal Craton at 1.3 Ga. It is considered a part of the Pilanesberg Alkaline Province, as it contains similar rock types such as nepheline syenites, ijolites and carbonatites and has a similar age. The carbonatite component of the Spitskop Complex consists primarily of dolomite carbonatite, calcite-dolomite carbonatite and calcite carbonatite with an apatite-rich zone. The outer part of the complex comprises alkaline rocks including ijolite and nepheline syenite, surrounded by the Rustenburg Layered Suite and the Lebowa Granite Suite of the Bushveld Complex. It is a unique complex, where both felsic and mafic fenites occur together. REE mineralization is hosted in carbonatites, however it is not considered an economic mineral deposit. This study characterizes the alteration stages that led to the formation of fenites and alkaline rocks, and the petrology and geochemistry of the Spitskop Complex. It shows that the fluids controlled the rare earth element content of Spitskop and affected the mobility of REE. The Spitskop Complex was mapped and samples were collected from different lithologies. Thin section petrology was used to determine the characteristic features and distribution of minerals. A total of 125 polished thin sections were studied using transmitted-reflected light microscopy and scanning electron microscopy (SEM). XRF and ICP-MS data of rocks have been obtained and the distribution of major-, trace- and rare earth elements of different lithologies were studied. The chemical composition of the fenitized Bushveld rocks have been compared with the unfenitized Bushveld rocks. The carbonatites all have similar major element concentrations except for CaO, MgO and MnO. The CaO and MgO concentrations reflect the type of carbonatite and the carbonatite mineralogy. Trace element and REE patterns of the different carbonatites are similar. The REE content of Spitskop carbonatites is up to 740 ppm. Nepheline syenites show metasomatic REE alteration patterns. Fenites are divided into two groups in the Spitskop Complex, mafic fenites and granite fenites. Mafic fenites represent metasomatized Upper Zone gabbro, whereas granite fenites represent metasomatized Nebo Granite. Moreover, granite fenites are subdivided into feldspar fenite, 4 which contains mostly feldspar; and quartz-feldspar fenite, which contains quartz and feldspar together. Mafic fenites are enriched in Na2O-K2O and P2O5 relative to the likely parental Upper Zone gabbros. Most of the trace element and all of the REE content of the mafic fenites are higher than the Upper Zone gabbros except Sc, V, Ni, Cu and U. Feldspar fenites are enriched in Na2O, K2O and MgO, and depleted in SiO2 compared to the parental Bushveld Granites. There are only some limited locations in the world where mafic and granitic rocks are extensively metasomatized together, therefore the Spitskop Complex is an ideal place to investigate the metasomatic geochemical processes. The mobility of the trace elements changes with increased fenitization. Nebo Granite has the highest trace elements concentrations, rather than in the quartz-feldspar fenite, with the feldspar fenite most depleted. However Cu, Sc and Eu are depleted in Nebo Granite. The REE data shows that the fenites compositionally lie between the unaltered Nebo Granite and the unaltered Upper Zone rocks. Fenitized Nebo Granite is depleted in REE and fenitized Upper Zone rocks are enriched in REE. The unaltered Upper Zone country rocks defines the lower REE boundary and the Nebo Granite defines the upper REE abundances. It is suggested that the metasomatic fluids caused a depletion of REE in the felsic rocks, whereas the same fluids caused an enrichment of REE in the mafic rocks. In mafic rocks the enrichment is dispersed through the whole rock across a broad zone and is therefore not economic. The data from thin section petrography and SEM suggests that the fenitization evolved in multiple steps at the Spitskop Complex. Alteration minerals show that there is a systematic change of minerals, from plagioclase to albite or nepheline, from olivine and orthopyroxene to clinopyroxene, from nepheline to analcite and from clinopyroxene to amphibole, which represent mafic fenites. Geochemical data, particularly REE patterns, suggests that the nepheline syenite at Spitskop is not a magmatic nepheline syenite, rather it is a product of fenitization. The REE patterns of the nepheline syenites are similar to the fenites of the Spitskop Complex and differ from other Pilanesberg nepheline syenites such as those in Pilanesberg, which are not fenitized. REE geochemistry also suggested that the syenites produced from fenitization (feldspar fenites) can be distinguished from magmatic syenite with the same REE patterns.
A full thesis submitted in fulfilment of the requirements for a Master degree in Geology, School of Geosciences, University of the Witwatersrand, Johannesburg, 2019
Keywords: Mineralogy; Rare earths